X-linked Parkinsonism with Intellectual Disability caused by novel mutations and somatic mosaicism in RAB39B gene. (November 2017) - Ciammola, Andrea; Carrera, Paola; Di Fonzo, Alessio; Sassone, Jenny; Villa, Roberta; Poletti, Barbara; Ferrari, Maurizio; Girotti, Floriano; Monfrini, Edoardo; Buongarzone, Gabriele; Silani, Vincenzo; Cinnante, Claudia Maria; et al.
Abstract: Background: RAB39B pathogenic variants cause X-linked Parkinsonism associated with Intellectual Disability, known as Waisman syndrome, a very rare disorder that has been mainly identified through exome sequencing in large Parkinson's disease cohorts. In this study we searched for pathogenic variants in RAB39B in two Italian families affected by X-linked early-onset Parkinsonism and Intellectual Disability. Methods: Three patients received neurological evaluation and underwent RAB39B sequencing. Results: Two novel RAB39B frameshift variants were found to result in the absence of RAB39B protein (family 1: c.137dupT; family 2: c.371delA). Patients showed unilateral rest tremor and bradykinesia; one of them also displayed an early-onset postural tremor. Paramagnetic substance deposition in the substantia nigra, globus pallidi, red nucleus, putamen and pulvinar was assessed by brain imaging. Two patients also showed moderate calcification of globus pallidi. Conclusion: In this study we highlight the evidence that X-linked early-onset Parkinsonism associated with Intellectual Disability occurs as a pattern of clinical and neuroimaging features attributable to RAB39B pathogenic variants. Highlights: Loss of RAB39B may lead to X-linked Parkinsonism with Intellectual Disability. Two novel RAB39B frameshift variants result in the absence of RAB39B protein. We discuss the syndromic Parkinsonism's variable expression that may affect women. We support the evidence that neuroimaging adds specific features to the syndrome. RAB39B somatic mosaicism may be important for unravelling Parkinson's disease.